Nanoformulation of Seaweed Eisenia bicyclis in Albumin Nanoparticles Targeting Cardiovascular Diseases: In Vitro and In Vivo Evaluation - Sofia Pinto; Maria Manuela Gaspar; Lia Ascensão; Pedro Faísca; Catarina Pinto Reis; Rita Pacheco (Marine Drugs, 2022)
Natural products, especially those derived from seaweeds, are starting to be seen as effective against various diseases, such as cardiovascular diseases (CVDs). This study aimed to design a novel oral formulation of bovine albumin serum nanoparticles (BSA NPs) loaded with an extract of Eisenia bicyclis and to validate its beneficial health effects, particularly targeting hypercholesterolemia and CVD prevention. Small and well-defined BSA NPs loaded with Eisenia bicyclis extract were successfully prepared exhibiting high encapsulation efficiency. Antioxidant activity and cholesterol biosynthesis enzyme 3-hydroxy-3 methylutaryl coenzyme A reductase (HMGR) inhibition, as well as reduction of cholesterol permeation in intestinal lining model cells, were assessed for the extract both in free and nanoformulated forms. The nanoformulation was more efficient than the free extract, particularly in terms of HMGR inhibition and cholesterol permeation reduction. In vitro cytotoxicity and in vivo assays in Wistar rats were performed to evaluate its safety and overall effects on metabolism. The results demonstrated that the Eisenia bicyclis extract and BSA NPs were not cytotoxic against human intestinal Caco-2 and liver HepG2 cells and were also safe after oral administration in the rat model. In addition, an innovative approach was adopted to compare the metabolomic profile of the serum from the animals involved in the in vivo assay, which showed the extract and nanoformulation’s impact on CVD-associated key metabolites. Altogether, these preliminary results revealed that the seaweed extract and the nanoformulation may constitute an alternative natural dosage form which is safe and simple to produce, capable of reducing cholesterol levels, and consequently helpful in preventing hypercholesterolemia, the main risk factor of CVDs.